2018
DOI: 10.1155/2018/7879895
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Directionality Found in Frontal-Parietal Attentional Networks

Abstract: Research in last few years on neurophysiology focused on several areas across the cortex during cognitive processing to determine the dominant direction of electrical activity. However, information about the frequency and direction of episodic synchronization related to higher cognitive functions remain unclear. Our aim was to determine whether neural oscillations carry perceptual information as spatial patterns across the cortex, which could be found in the scalp EEG of human subjects while being engaged in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Frontal beta coherence is shown to support control of the frontal eye fields [26], and the increases in Fp1-Fp2 and F3-F4 frontal beta coherences could, therefore, be indicative of increased oculomotor control in our subjects, an obvious skill enhancement that might be entrained by academic challenges requiring a lot of reading. Parietal beta activity at P3-P4 is shown to support attentional control and short-term memory functions [27]. The increase in P3-P4 beta coherence with eyes open which we observed is consistent with what would be predicted for an intense academic challenge requiring enhancement of attentional control and short-term memory functions.…”
Section: Behavioural Neurologysupporting
confidence: 89%
“…Frontal beta coherence is shown to support control of the frontal eye fields [26], and the increases in Fp1-Fp2 and F3-F4 frontal beta coherences could, therefore, be indicative of increased oculomotor control in our subjects, an obvious skill enhancement that might be entrained by academic challenges requiring a lot of reading. Parietal beta activity at P3-P4 is shown to support attentional control and short-term memory functions [27]. The increase in P3-P4 beta coherence with eyes open which we observed is consistent with what would be predicted for an intense academic challenge requiring enhancement of attentional control and short-term memory functions.…”
Section: Behavioural Neurologysupporting
confidence: 89%
“…We have found instances from mTBI that have caused a loss of alpha activity, which may implicate similar deficiencies in the attentional states found in the frontal-parietal networks. The alpha bandwidth has been associated with attentional states, specifically found in the frontal-parietal networks [ 7 , 13 , 38 , 39 , 40 , 41 , 42 ]. Alpha rhythms seem to be regulated during activities when an individual is focused on a given task [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…VEPs measure the processing of the visual system, which features two major pathways: the parvocellular (P) pathway, originating in the midget retinal ganglion cells (RGCs); and the magnocellular (M) pathway, originating in the parasol RGCs [ 5 , 6 ]. These pathways are associated with specific functions, conveying the ‘‘what’’ (visual areas (V1)-(V3)-(V4)-inferior temporal cortex (IT)) and ‘‘where’’ ((V1)- > (V2)- middle temporal area (MT)-superior temporal sulcus (STS)) of visual information [ 7 , 8 ]. Finally, the ventral stream is fed by the PC cells, whereas the dorsal stream is fed by the MC cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has revealed the consistent nature by which attention can be measured using neuroimaging techniques [54][55][56][57], particularly within the visual domain. Specifically, a large portion of this research implies that decreases in, or the suppression of, alpha activity is positively correlated with the strength of attention towards a stimulus [58][59][60].…”
Section: Introductionmentioning
confidence: 99%